A Deeper Understanding of Metacomprehension: Development of a New Multidimensional Tool - Christian Soto; Antonio P. Gutierrez de Blume; Rodrigo Asun; Matthew Jacovina; Claudio Vasquez (EARLI, 2018)
The purpose of this research endeavor was to develop and validate a new measurement tool predicated on previous research to assess learners' metacomprehension during reading. In two separate studies (N = 923) with Chilean undergraduate students, we demonstrate the versatility and utility of our proposed Metacomprehension Inventory (MI). In Study 1, we provide empirical support for the psychometric soundness and construct validity of the MI. In Study 2, we provide evidence of the measurement invariance of the MI between males and females. Results of Study 1 revealed the hypothesized factor structure of the MI is sound, with high factor loadings, excellent model fit, and moderate-to-strong inter-factor correlations. Study 2 results indicated that the MI is interpreted similarly by both males and females, as factor loadings were largely statistically identical across the two groups. We discuss implications of our proposed MI for theory and applied research.